CHALLENGES AND ISSUES IN BIG DATA - Krithika, M.Meena; Parameswari, K.Kannika; Gayathri, K. (IJRDO -Journal of Computer Science Engineering, 2016)
The espouse of data-driven determinationmaking is being conceived broadly, andthere is enlarging excitement for the idea of"Big Data". While the espouse of Big Datais genuine, there is parallel gap within itspotentiality and its attainment.Heterogeneity, complexity, timeliness,progress, and recession problems with BigData prevent proceeding at all stages of thepipeline that can produce value from data.The obstacle starts instantly during dataappropriation, when the data obligate us tomake determination currently in an ad hocmanner. Most of the data is not related instructured format.The assessment of data blow up when it canbe combined with another data, thus dataadherence is a greater creator of evaluation.Since many data is instantaneouslyoriginated in digital format today and wehave the scope and denounce to persuade thecreation to propitiate subsequently and toautomatically link previously completeddata. Data analysis, association, gatheringand modeling are other basic challenges.Data analysis is a open bottleneck in severalapplications, both due to requirement ofscalability of the domestic algorithms anddue to the complication of the data thatneeds to be resolved.The many unique challenges andopportunities comparable with Big Datainvolve rethinking several outlooks of thesedata management stages, while maintainingother beneficial aspects. We conclude thatparticular investment in Big Data will leadto a new wave of fundamental technologicalgrowth that will be embodied in the nextorigination of Big data management andanalysis platform.We conclude that these research issues arenot only instant, but also have the ability tocreate large economic value in the economyfor years to come. However, they are alsodifficult and requiring us to rethink dataanalysis systems in crucial ways. Adominant investment in Big data, efficientlydirected, can flow not only in majorscientific advances, but also lay the footingfor the next origination of advances inmedicine, science, and business.